(untitled) (BIRDEM Medical Journal, 2017)
Background: The term gestational diabetes mellitus (GDM) is becoming a major health problem in developing countries undergoing rapid changes in lifestyle, dietary habits and body mass index. GDM is associated with an increased incidence of congenital abnormalities which is also aggravated by mother’s zinc and copper deficiency. Zinc and copper are essential trace elements for normal embryogenesis and fetal growth and their deficiency increase mortality and morbidity of mothers, embryos and neonates. This study was designed to evaluate the association of serum zinc and copper with GDM in second and third trimester. Methods: It was a case-control study. This study was conducted in Mymensingh Medical College Hospital during the period from July 2013 to June 2014 to evaluate the association of zinc and copper levels of pregnant women with GDM. A total induded of 172 subjects were participated in this study; among them 86 women diagnosed with GDM were selected as case (Group-I) and 86 healthy pregnant women were control (Group- II).The case group was again subdivided as Group Ia and Ib according to second and third trimester respectively. Control group was also subdivided as Group IIa and IIb according to second and third trimester respectively. Student’s unpaired ‘t’ test was used to analyse the data between groups. For analytical purpose 95% confidence limit (p<0.05) was taken as level of significance. Results: There was significant difference in serum zinc and copper levels in cases compared to control group. Highly significant difference (p<0.001) was found when serum zinc was compared between women with GDM and normoglycemic pregnant women in second and third trimester. Serum copper level was significantly increased in cases compared to control group in second trimester and the difference was found highly significant (p<0.001) and significant difference (p<0.01) was found in GDM compared to normoglycemic pregnant women in third trimester. Birdem Med J 2018; 8(1): 52-55